Adaptive Energy Management Control for Efficiency Improvement of Supercapacitor-Based Energy Recovery System - Ģirts Staņa; Martin Makar; Kaspars Kroičs (Energies)
The efficiency of the DC microgrid can be improved by adding additional energy storage to recover regenerative braking energy. Supercapacitors are well suited for such applications. To make such devices easily connectable to the existing grid, it is beneficial to measure the voltage of the DC bus. The paper proposes a method on how to estimate load current indirectly from this voltage measurement. Estimated current is used in the developed energy management algorithm that adapts current reference of an energy storage system to discharge stored energy in the most energy efficient way. The paper presents simulation and experimental results and shows in some cases efficiency improvement even by more than five percent.